Tipong Pinoy Manila & Intramuros - National Commission on Culture and the Arts (Philippines).; GMA Network, Inc.; LC Purchase Collection (Library of Congress) ([Quezon City GMA Network, 1998)
A television program about Manila during the revolution, including features on Intramuros and Pasig River.
Summary taken from container.
Sources used: videodisc container; cataloging record from OvOp field office.
In Tagalog.
Keywords: Television